2015
DOI: 10.1103/physrevd.91.124026
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance in stars

Abstract: It has long been known that dissipation is a crucial ingredient in the superradiant amplification of wavepackets off rotating objects. We show that, once appropriate dissipation mechanisms are included, stars are also prone to superradiance and superradiant instabilities. In particular, ultra-light dark matter with small interaction cross section with the star material or self-annihilation can trigger a superradiant instability. On long timescales, the instability strips the star of most of its angular momentu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…However, superradiant effects are not limited to rotating black holes and in fact can appear in any classical system that is able to absorb radiation [12,14,15,22,33,34]. In this work, we show that superradiance also occurs in the presence of rotating and conducting spheres, and most notably in (rotating) stars with nonzero conductivity.…”
Section: Superradiance In Starsmentioning
confidence: 66%
“…However, superradiant effects are not limited to rotating black holes and in fact can appear in any classical system that is able to absorb radiation [12,14,15,22,33,34]. In this work, we show that superradiance also occurs in the presence of rotating and conducting spheres, and most notably in (rotating) stars with nonzero conductivity.…”
Section: Superradiance In Starsmentioning
confidence: 66%
“…equation (2a). Such term was indeed used by Zel'dovich in his seminal study and can be shown to mimic accurately the correct description of many superradiant systems [32][33][34][35]. Such a Lorentz-invariance-violating term introduces a superradiantlike instability, with a timescale on the order 1=C, which we can tune to be within our numerical limits.…”
mentioning
confidence: 71%
“…Finally, we have focused solely on scattering in this work, but it is well known that superradiance can also manifest as an instability that triggers the exponential growth of bound states around Kerr black holes [37][38][39][40][41][42][43][44][45] and other astrophysical bodies [12,13,46]. A similar instability is likely to be present in black hole binaries and will be the subject of a forthcoming paper.…”
Section: Discussionmentioning
confidence: 99%
“…Case in point: In his seminal papers on the subject [8,9], Zel'dovich describes the amplification of electromagnetic waves by a conducting cylinder; while more recently, Torres et al reported the first laboratory observation of superradiance in water waves scattered by a draining vortex [10]. Superradiant scattering by rotating stars has also recently been studied [11][12][13].…”
Section: Introductionmentioning
confidence: 99%